Rapidly destructive coxopathy due to dialysis amyloidosis: a case report. (3rd April 2021) - Nakano, Shiho; Nakajima, Arata; Sonobe, Masato; Yamada, Manabu; Takahashi, Hiroshi; Aoki, Yasuchika; Terai, Kensuke; Hiruta, Hiroyuki; Nakagawa, Koichi
Abstract: Rapidly destructive coxopathy (RDC) is a disease that is sometimes seen in geriatric patients. A total hip arthroplasty (THA) is mostly chosen to treat the RDC, but few cases are known that received THAs due to RDC associated with dialysis amyloidosis. We report a case of RDC due to dialysis amyloidosis with special references to its pathophysiology. The case involved a 61-year-old male who had been on dialysis for seven years due to diabetic nephropathy. At his first visit, the radiographs showed collapse and flattening of the femoral head, which progressed within a month. Magnetic resonance imaging for the hip disclosed bone marrow edoema of the acetabulum and sclerosis of the subchondral bone of the femoral head. Biochemical analyses for the blood revealed high inflammatory reactions with elevated C-reactive protein and white blood cell count, but the joint fluid cultures were negative for general bacteria, tubercle bacillus, and nontuberculous mycobacteria. As he did not have gastrointestinal disorders or inflammatory arthritis other than the left hip and no disease that caused elevated inflammatory reactions was observed, we diagnosed the patient with RDC due to dialysis amyloidosis, and a THA was performed. Pathological findings for the synovium collected during surgery showed infiltration of the inflammatory mononuclear cells and vascular hyperplasia. The synovial tissues were extensively stained with an antibody to β2-microglobulin. Many tartrate-resistant acid phosphatase-positive multinucleated cells were also observed in the synovium. One year after surgery, his left hip pain disappeared and he returned to work.